STABILITAS STATIS DAN DINAMIS KAPAL LATIH DAN PENELITIAN STELLA MARIS (Static and Dinamic Stability of The Research Training Vessel, Stella Maris) - Aldin Muhammad; Budhi Hascaryo Iskandar (Buletin PSP, 2007)
This paper explains the quality of static stability of The Research Training Vessel Stella Maris from the variation of vertical centre of gravity (G) and variation of draft values point of view. This explanation started with the influence of the main dimension ratios, and then continued by the explanation of the hydrostatic parameters and ended with the main explanation of the static stability of the ship. The analysis result of themain dimension ratios shows that few ratios give different effect to few abilities of the ship. The analysis result of the hydrostatic parameters gives informations about static body descriptions of Stella Maris and also the pruperness of its design. The result shows that her static stability has been fulfilled the international safety rules by International Maritime Organization (IMO). The critical value of static stability from the variation of KG is at KG 2,1 m, meanwhile there is 1W critical value for all draft variation. The critical value for the draft could be above the maximum draft in this analysis.Keywords: static stability, hydrostatic parameters, main dimention ratios